Picky predators and odd prey: colour and size matter in predator choice and zebrafish's vulnerability – a refinement of the oddity effect. Issue 2 (3rd March 2020) - Aivaz, Angela N.; Manica, Andrea; Neuhaus, Peter; Ruckstuhl, Kathreen E.
Abstract : Many fish species typically assort into homogeneous groups and thus reduce the risk of predators targeting individuals that are phenotypically odd compared to the majority of the group. The confusion and oddity effect hypotheses predict, that phenotypically odd individuals in a group are preferentially targeted by predators. Therefore, heterogeneous groups of prey should be more vulnerable to predator attention and attacks than homogeneous (all prey is the same colour, size, etc.) groups. Predators might use different cues to select a target, depending on their sensory abilities (sound, smell, vision, etc.). Visual-hunting predators that can see colour, for example, may be more likely to select prey based on colour than size oddity of prey. Previous studies on the oddity effect have found support for the colour-oddity and predator response, and to a lesser extent on size oddity. We thus predicted that, given a choice, a group with an odd-coloured individual would be targeted more often by a predator than a group with an odd-size fish but not odd in colour. Heterogeneous groups of six zebrafish ( Danio rerio ) containing either one odd-coloured (wildtype or red) or one odd-sized (large or small) individual were used as stimulus prey in dichotomous choice experiments examining prey preference in needlefish ( Xenentodon cancila ). Needlefish preferred heterogeneous groups regardless of the colour of the odd individual and when the odd individual was smaller than the other group members. However, when the odd individual was larger than the rest of the group, the predators preferred homogeneous groups of small fish. These new findings are inconsistent with the predictions of the oddity effect and warrant investigation of alternative hypotheses for size-assorted grouping in fish.